Engineering Properties of Tamarind: A Comparison Between Shelled and Unshelled Tamarind - Verma, Karishma; Gupta, Suchita V.; Patil, Bhagyashree; Bakane, Pramod H.; Bharad, S. G. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during April–June, 2024 in the department of Agricultural Process Engineering, Dr. Panjabrao Deshmukh Krishi Vidhyapeeth Akola, Maharashtra, India to determine the physical, chemical and frictional properties of shelled and unshelled tamarind. Standard methods are used to calculate all the engineering properties. Moisture content was determined by hot air oven method and the color was determined by digital colorimeter. The obtained results of the study were: the mean length, width and thickness of unshelled and shelled tamarind were 81.36 mm, 22.31 mm, 15.28 mm and 75.01 mm, 17.41 mm, 10.24 mm respectively. The mean bulk density, true density and porosity of unshelled and shelled tamarind were 370.01 kgm-3, 719.7 kg m-3, 48.39 % and 512.35 kg m-3, 912.73 kg m-3, 43.49% respectively. The mean arithmetic Mean Diameter, Geometric Mean Diameter, sphericity index, surface area of unshelled and shelled tamarind were39.65mm, 30.02mm, 0.38, 2866.80 mm2 and 34.22 mm, 23.45 mm, 0.332, 1754.24 mm2 respectively. The mean moisture content and color values of unshelled and shelled tamarind are 23.64%, L*=47.606, a*=8.944, b*=21.604 and 23.14%, L*=37.178, a*=11.22, b*=20.404 respectively. This study analyzed the critical differences between the engineering properties of unshelled and shelled tamarind fruit, providing valuable insights for optimizing the design and operation of machinery used in tamarind processing. Understanding these properties can improve handling, reduce processing losses, and enhance the efficiency of equipment used in cleaning, sorting, and packaging.